P PELATIHAN PENCEGAHAN ADIKSI GAME PADA GURU BK SMP SE KOTA BATU: - - Denok Setiawati Warsongko; Eko Darminto; Najlatun Naqiyah; Evi Winingsih (Transformasi dan Inovasi : Jurnal Pengabdian Masyarakat, 2022)
This training aims to improve the competence of counselors in preventing game addiction in students with collaborative guidance. This solution was taken due to the phenomenon of increasing this training using the game addiction method, especially as technology develops and the covid 19 pandemic period. The training stages begin with material presentation, model demonstration, supervision and evaluation practices. The subjects of the training were 47 teachers of guidance and counseling throughout the city of Batu. The data collection method is self report. The self report contains the experience of practicing collaborative guidance, the chosen form of guidance, the stages of guidance and evaluation. Data analysis used descriptive analysis. The results of the training show an increase in competence in mastering academic and professional competencies in preventing game addiction with collaborative guidance. Evaluation results show that training is considered very useful 54.2%, 45.8% useful. Participants' views on the team's ability to provide training and coaching are 37.5% mastery, 62.5% mastery. Furthermore, ongoing training activities such as family counseling for the prevention of game addiction can be carried out.